Dynamic changes in the levels of sCD62L and SPARC in chronic myeloid leukaemia patients during imatinib treatment - Elkholy, Mahmoud Mohamed; Fahmi, Maryan Waheeb; El‐Haggar, Sahar Mohammed (Journal of clinical pharmacy and therapeutics, 2022)
What Is Known and Objective Chronic myeloid leukaemia (CML) microenvironment is responsible for resistance of leukaemic cells to tyrosine kinase inhibitor, altered adhesion, increased proliferation and leukaemic cells growth and survival through the secretion of many soluble molecules. We aimed at monitoring soluble L‐selectin (sCD62L) and secreted protein acidic and rich in cysteine (SPARC) levels in chronic phase chronic myeloid leukaemia (CP‐CML) patients and assessing the impact of imatinib on these parameters. Methods This prospective controlled clinical trial enrolled 35 subjects classified into two groups: control group included 10 healthy volunteers and CP‐CML patients group included 25 newly diagnosed CP‐CML patients received imatinib 400 mg once daily. sCD62L plasma levels, SPARC serum levels, breakpoint cluster region‐Abelson1 (BCR‐ABL1) %, complete blood count with differential, liver and kidney functions parameters were assessed at baseline and after 3 and 6 months of treatment. Results and Discussion At baseline, sCD62L and SPARC were significantly elevated in CP‐CML patients (p < 0.05) compared to control group. After 3 months of treatment, sCD62L was non‐significantly decreased (p > 0.05), while surprisingly SPARC was significantly increased (p < 0.05) compared to baseline. Moreover, after 6 months of treatment, sCD62L was significantly decreased (p < 0.05) and SPARC was non‐significantly decreased (p > 0.05) compared to baseline. In addition, sCD62L was significantly correlated with WBCs and neutrophils counts, while SPARC was significantly correlated with lymphocytes count at baseline and after 3 and 6 months of imatinib treatment. What Is New and Conclusion The elevated levels of sCD62L and SPARC at diagnosis in CP‐CML patients could reflect their roles in CML pathogenesis and the dynamic changes in their levels during imatinib therapy might suppose additional mechanisms of action of imatinib beside inhibition of BCR‐ABL. Furthermore, imatinib showed a significant impact on sCD62L and SPARC levels during treatment period. The microenvironment of CML is critical for disease persistence and responsiveness to treatment. Due to resemblance to normal stem cells, CML leukaemic stem cells could present in the same microenvironment, where a reciprocal association between these cells and bone marrow microenvironment is correlated with enhanced proliferation, quiescence, altered adhesion and treatment resistance. All these mechanisms are done by group of adhesion molecules or by production of many soluble molecules. In this study, sCD62L and SPARC levels were significantly elevated in CP‐CML patients at baseline and imaitnib showed significant changes in their levels after 3 and 6 months of treatment. sCD62L was significantly correlated with WBCs and neutrophils counts before and after 3 and 6 months of treatment, while SPARC was significantly correlated with lymphocytes before and after 3 and 6 months of treatment. On contrary, BCR‐ABL1% did not show any correlation with sCD62L or SPARC. Results from this study suggest that the elevation of sCD62L and SPARC levels in CP‐CML patients at baseline might refer to their attribution to CML pathogenesis and the changes in their levels during imatinib treatment period might suppose additional mechanisms of action of imatinib in addition to BCR‐ABL inhibition.